The Scope Of Three-Dimensional Digital Visualization Systems In Vitreoretinal Surgery - Agranat JS (Dove Medical Press, 2019)
Joshua S Agranat,1 John B Miller,1 Vivian Paraskevi Douglas,1 Konstantinos AA Douglas,1 Anna Marmalidou,1 Matthew A Cunningham,2 Samuel K Houston III2 1Retina Service, Massachusetts Eye and Ear, Department of Ophthalmology, Harvard Medical School, Boston, MA, USA; 2Florida Retina Institute, Orlando, FL, USACorrespondence: Samuel K Houston IIIFlorida Retina Institute, 95 Columbia Street, Orlando, FL 32806, USATel +1 407-404-1597Email shouston@floridaretinainstitute.comIntroduction: Significant advances in three-dimensional (3D) imaging technology have allowed for the incorporation of 3D digital displays into medical and surgical devices. Despite initial adoption of the NGENUITY® 3D Visualization System in vitreoretinal surgery, there are limited publications regarding its use. The generally accepted main benefits include improved ergonomics, enhanced surgical team communication and education, reduced retinal phototoxicity, increased depth of field, and display image manipulation. Despite these potential benefits, many retina specialists have questioned its universal applicability to a wide variety of vitreoretinal surgeries.Objective: To report on the variety of indications and surgical efficacy of the NGENUITY® 3D Visualization System in vitreoretinal surgery via a review of surgical experience at two vitreoretinal practices in both the academic and community settings.Methods: A retrospective review was conducted of consecutive surgical cases performed on the NGENUITY® 3D Visualization System at Massachusetts Eye and Ear Infirmary and Florida Retina Institute from June 1st, 2017 to November 1st, 2018. Age, presenting diagnosis, surgical procedure, and intraoperative details were recorded.Results: 272 vitreoretinal surgeries on the Alcon NGENUITY® 3D Visualization System were identified between June 1st, 2017 and November 1st, 2018 at the participating institutions. A detailed breakdown of the indications for surgery and related procedures is reported. During all 272 cases on the 3D digital system, there were no complications attributed to the visualization system.Conclusion: This series illustrates the diversity of vitreoretinal surgeries that can be performed on this system without compromising surgical viewing or increasing surgical complications. The Alcon NGENUITY® 3D Visualization System possesses favorable ergonomics, illumination levels, depth of field, display filters, and trainee experience.Keywords: heads-up display, 3-D Visualization, NGENUITY, retina, surgery